Real-Life Effectiveness and Tolerance of Baricitinib for the Treatment of Severe Alopecia Areata with 1-Year Follow-Up Data - Axel De Greef; Romane Thirion; Pierre-Dominique Ghislain; Marie Baeck (Adis, Springer Healthcare, 2023)
Abstract Introduction The efficacy of conventional treatments for alopecia areata (AA) has been extremely variable and disappointing, with a high rate of relapse. Recent clinical trials and real-life studies have demonstrated efficacy and safety of baricitinib (an oral Janus kinase 1 and 2 inhibitor) in alopecia areata. Methods We retrospectively evaluated the effectiveness and tolerance of baricitinib in alopecia areata in a real-life Belgian monocentric adult cohort. The primary outcome was evaluated by the percentage of patients who achieved a Severity of Alopecia Tool (SALT) score of ≤ 20 at the end of the follow-up. All treatment-emergent adverse events were collected. Results In this 19-patient series, with a median ± interquartile range (IQR) follow-up duration of 13 ± 16.2 months, we demonstrated that: (i) hair regrowth was observed in nearly 90% of patients between 4 and 16 weeks after initiation of baricitinib; (ii) at the end of the follow-up, more than 70% and, in particular, 100% of patients with patchy AA, reached the primary outcome (SALT score ≤ 20); (iii) almost half of the patients, mostly with patchy AA, showed a complete hair regrowth (SALT score = 0), within a median ± IQR treatment time of 8.5 ± 10 months; (iv) baricitinib was discontinued in three patients with total hair regrowth, two of whom relapsed; and (v) no serious adverse events were reported. Conclusion Baricitinib is effective in treating patients with alopecia areata, particularly for the patchy phenotype, but with a risk of relapse after discontinuation. Safety data are reassuring, with lipid changes being the most frequent adverse event.